Atrocities against the Kuki People in the Manipur Conflict: An In-Depth Analysis of Its Impact on Kuki Society - Haokip, Sonkhothang (UIN Sunan Gunung Djati Bandung, 2025)
In northern India, the tension between the Kuki and Meitei/Meetei ethnic groups is referred to as the Manipur problem. The Meiteis, who are already included under the General, OBC (Other Backward Classes), and SC (Scheduled Castes) categories, are clamoring to be granted ST (Scheduled Tribes) status. The tension brewed in May 2023 when the Manipur High Court recommended giving ST status to Meiteis. Opposing this, the Kuki and Naga population, which already enjoy ST status, held major peaceful protests against this proposal. But violence erupted on May 3, 2023, when the Meiteis torched the Anglo-Kuki Centenary gate in Churachandpur District, which resulted in increased strife in the area. The study seeks to investigate the primary elements and incidents of the Kuki people during the Manipur conflict. The scope of the study is to present an exposé on the most tragic incident that befell the Kukis and the weapons pillaged by the Meiteis during the conflict. This study performs an exhaustive review of secondary sources between 2023 and 2024, including websites, news outlets, YouTube channels, and particular sources like The Hill Journal, the Kuki Students Organization (KSO) Media and Documentation Cell, and so on. Both qualitative and quantitative content analysis techniques were used, including topic identification and coding to organize the findings. As a consequence of the conflict, weapons are plundered; Kuki men and women are set on fire, exhibited nude, raped, harassed, tortured, shot, and murdered. In addition, there are killings, injuries, IDPs (Internal Displaced Persons), and villages, homes, churches, and offices of NGOs (Non-Governmental Organizations) burned. To end the trauma and agony inflicted on this community, the research concludes that responsibility, justice, and healing are imperatively and urgently required.